Depression and Anxiety in Adolescent Females: The Impact of Sleep Preference and Body Mass Index - Pabst, Stephanie R. (2009)
PURPOSE: To examine the differences in depressive symptoms and anxiety between (a) normal weight and overweight, and (b) morning type and evening type (sleep chronotype) adolescent girls. The interaction of sleep chronotype and weight and depressive symptoms and anxiety were also examined. METHOD: The design consisted of a cross-sectional study of 264 adolescent females (mean age= 14.9 ± 2.2, range 11–17 years). Sleep chronotype, depressive symptoms, and anxiety were obtained by self-report questionnaire. The mean of three measurements of height and weight was used to calculate the body mass index (BMI). BMI was plotted on the CDC BMI-for-age growth charts to obtain percentile ranking. Participants were categorized into two groups according to BMI percentile: normal weight (<85th percentile) and overweight (≥85th percentile). RESULTS: Compared with normal-weight females, overweight females were more likely to be non- Caucasian, lower socioeconomic status, have more advanced pubic hair and breast stages, and earlier age at menarche. No differences were observed with respect to sleep chronotype, depressive symptoms, and trait anxiety between normal weight and overweight females. Evening chronotype was associated with more depressive symptoms (β = −.65, p < .01) and higher trait anxiety (β =−.22, p < .05). Evening chronotype was associated with more depressive symptoms in both normal-weight and overweight females. However, the association was stronger in overweight females. CONCLUSIONS: Individually, sleep and weight impact physical and mental health during adolescence. The combination of evening chronotype and overweight appears to have the strongest association on the emotional health of adolescent females. Further investigations are needed to provide potential biological mechanisms for this relationship.